EXSISTENCE iSYATTARIYAH iTAREKAT IN iTALANG iTIGE VILLAGE MUARA iKEMUMU iDISTRICT, REGENCY iKEPAHIANG, BENGKULU PROVINCE - Tomi Saputra (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
The problem formulation in this research are: 1) What is the understanding of the people of Talang Tige Village about the Syattariah congregation? 2) What are the teachings of the Syattariyah congregation in Talang Tige Village? 3) iWhat iare ithe ifactors ithat isupport and ihinder ithe development of the sharia congregation in Talang Tige Village? 4) How does the sharia congregation influence the Talang Tige village community? This research uses a field research approach using qualitative methods. Data sources were obtained from congregants of the Syattariyah congregation and other documents. To obtain maximum results, this research uses data collection techniques in the form of observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and verification/conclusion. The results of this research conclude that: 1) The people of Talang Tige village understand that the Syattariyah order is a form of worship or teaching in strengthening monotheism through self-training in the form of practices according to the teachings of the Syattariyah order, 2) The teachings of the Syattariyah order, namely ba'iat, talqin, and dhikr which are read clearly/clearly, 3) One of the factors inhibiting the development of the Syattariyah order in Talang Tige village is the congregation's limited time to attend the al-Qur’an because they are busy working, 4) Through the order taught by the murshid, is able to provide benefits on how to cleanse themselves and practice practices that enable them to control themselves and abandon bad habits that can harm others.